Surveying with a bird s eye view - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Simple construction surveying for rural applications By J H Loedeman, co-publication Agromisa CTA, Agrodok No. 6. 2000. 96 pp. ISBN 90 727 46 96 1 CTA number 261. 5 credit points